Experimental Validation of a Novel Generator of Gas Mixtures Based on Axial Gas Pulses Coupled to a Micromixer - Florian Noël; Claire Trocquet; Christophe A. Serra; Stéphane Le Calvé (Micromachines, 2021)
In this work, a novel generator of gas mixtures previously numerically investigated and based on axial gas pulses coupled to a micromixer has been conceived, manufactured, and validated. Standard gaseous pollutant mixtures and pure nitrogen or pure air were introduced in a microdevice designed to generate alternating axial gas pulses which were downstream homogenized by means of a multi-stage modular micromixer. The dilution, and therefore the final pollutant concentration, was controlled by two parameters: the ratio between the times of each of the two gas pulses and the partial pressure of the pollutant(s) mixture added to the device. The gas mixture generator was coupled to an analyzer to monitor the concentration of aromatic pollutants. The response time was optimized to be lower than 2 min in accordance with the analytical instrument. The quantity of pollutants measured at the micromixer’s outlet increased linearly with the expected gas concentration of 3.7–100 ppb generated by this novel microfluidic generator and fitted perfectly with those obtained by a reference gas dilution bench. At 5 ppb, the precision on the concentration generated is close to that obtained with the conventional gas mixing bench, i.e., around 10%.